Residual stresses created during curing of a polymer matrix composite using a viscoelastic model. (17th June 2016) - Zhang, J.T.; Zhang, M.; Li, S.X.; Pavier, M.J.; Smith, D.J.
Abstract: A modified viscoelastic constitutive model is proposed to predict cure-induced residual stresses in polymer matrix composites. The modifications rely on using the inverse of the Deborah number to describe regimes corresponding to a fully relaxed state, a viscoelastic state and an elastic state. The composite is only in a viscoelastic state for limited ranges of the Deborah number. By considering the evolution of the Deborah number during curing of the AS4/3501-6 composite, the composite is in a fully relaxed state when it is cured at high temperature and the degree of cure is lower than 0.73, and no further changes in the viscoelastic characteristics when the degree of cure is higher than 0.8. A 3D simulation of a composite laminate plate is used to predict the evolution of the residual stresses. The analysis reveals that the accurate simulation on the cure-induced residual stress should include the last two states of the entire cure process, and consider the stress relaxation, thermal deformation and chemical shrinkage.